First and second-level digital divides and cultural capital: Framing digital lives of seniors in Portugal and Europe - Lapa, T.; Martinho, T; Reis, C. (9th International Conference on Human Aspects of IT for the Aged Population, ITAP 2023, held as part of the 25th International Conference on Human-Computer Interaction, HCII 2023, Proceedings, 2023)
Although research has been mainly focused on mapping individual determinants of digital exclusion, stressing the role of schooling, less attention has been paid to explore the role of pre-existing cultural practices and capital, beyond formal education, as determining factors of first-level and second-level divides among seniors and across western societies. The diffusion of digital devices with access to the internet is reaching a level close to 90% in European societies. However, the digital divide is still a noticeable issue when comparing generations and among seniors of age 65+ years (Friemel, 2016). As access to the internet, digital literacy, and use of digital services are increasingly prerequisites for public life and accessing public and commercial services in Europe and elsewhere (Alexopoulou, Åström, Karlsson, 2022), it is pertinent to look at the digital lives (or lack of) of seniors. Therefore, our study explores the influence of variations in cultural capital on the digital divide among seniors (aged 65+) in Portugal and Europe. The analyses are based on data from Eurobarometer and a representative survey concerning cultural practices on and offline in Portugal. The first part of the study introduces a comparative perspective of different regions of the European Union (EU) concerning the distribution of digital access and of online practices with cultural purposes, tracing digital first and second-level digital divides across Europe according to indicators of social and cultural inequality. The second section focuses on the results of the national survey regarding Internet use for cultural consumption. In the third part, also based on the same national data, we explore the association of various offline and online practices related to culture with types of digital divide. With this analysis we hope to find alternate ways of considering the links between technology usage and seniors and go beyond traditional analysis of this relationship.